THE EFFECT OF RESPONSIBILITY, WORK SATISFACTION, COMMUNICATION AND DISCIPLINE OF WORK ON EMPLOYEE PERFORMANCE IN THE OFFICE OF STIE IBNU SINA BATAM - Suyono Suyono (EQUILIBIRIA, 2019)
The purpose of this study is to find out (1) to determine the effect of responsibility on employee performance (2) to determine the effect of job satisfaction on employee performance (3) to determine the effect of communication on employee performance (4) to determine the effect of work discipline on employee performance (5) To find out the effect of responsibility, job satisfaction, communication and work discipline together on employee performance.                    The method that I use in the preparation of this thesis is descriptive analysis method, which is a research method with interview techniques, observation, literature study, and data sources. Whereas to analyze the data obtained, a comparison was made between the data in the field and the library data, then an analysis was made to draw conclusions.                    The results of research and data processing show that Based on the results of the t test, the variable responsibility (X1) has a significant effect on performance employee. job satisfaction has an effect on employee performance. communication communication had a significant effect on employee performance. work discipline has an effect on employee performance. responsibility, job satisfaction, communication and work discipline simultaneously have a significant effect on employee performance. Keywords: responsibility, job satisfaction, communication, work discipline and employee performance